Dinâmica geomorfológica de voçorocas no município de Tucano – Bahia - Pinto, Bismarque Lopes (2018)
The evolutionary and current understanding of the erosive scars in the landscape give support for a better understanding of the dynamics of the past and present natural environment so that their geomorphological behavior denounce the performance of the environmental factors in the process of relief sculpture. Thus, to better understand the erosive scars in their different stages, the objective was to analyze the geomorphological structures of 02 (two) gullies in the rural area of the city of Tucano (BA) to evaluate the evolutionary and contemporary dynamics of the erosive features exhibited in the area. In this sense, in order to fulfill these and other guiding objectives of the research, different methodological procedures were used, prioritizing the literature review, the fieldwork and thematic charts on the geoenvironmental conditioners of the gull perimeter and associated topographic profiles, between others. The results of this study show that the Voçoroca 01 has dimensions around 13,377 km², with a morphological ramified aspect, constituted of 04 secondary channels and standard disconnected the drainage network. It is located in the upper and middle third of the slope of the dominant board in the area. Its sectoral division made it possible to better understand the erosive dynamics with greater expressiveness between the upper thirds of greater erosion performance, covering an area around 9.12 km², and lower that is characterized by the accumulation of sediments occupying an area of approximately 4.24 km². The sectorization, undoubtedly, facilitated the identification of internal features of pedestals, residual kettles, ribs and scales. Finally, an average soil loss of approximately 2,453 m³ was recorded. In spite of Voçoroca 02, it was verified its sandy range corresponding to 10,97 km ². However, due to the fact that it presents an advanced evolutionary dynamics in relation to voçoroca 01, it has a rectangular configuration without the presence of secondary channels. In its sectorization, it was observed erosive focus of 9,008 km² predominating in the upper and middle thirds of the voçoroca that presents a system of internal morphologies with 08 regression alcoves at the top of the erosive scar, besides the formation of ducts, pedestals, furrows and ravines. In the lower portion of greater accumulation of sediments covering 1,971 km², an extensive consolidated sedimentation bank was found. Its positioning is disconnected from the drainage network, with soil loss estimated at 3,045 m³. Given the large size of the area, it is stated that the predominant voicoramento system in the rural area of the municipality of Tucano has its genesis associated with the joint interference of the natural processes in the evolution of the local tabuliform relief, even though the economic activities developed in the domain perimeter of the erosive scars, due to their expressivity on the ground, does not require an intensive use of the soil capable of reverberating in the rapid evolution of the local relief, except in a very secondary way, with almost imperceptible results. In summary, the results presented here serve as a basis for the implementation of an environmental planning policy, even by pioneering research, since the area has always been seen as a point of no use and of little interest from the point of view of local municipal management. Thus, due to the high degree of degradation reached by the area of the perimeter of the gullies, it is urgent to take measures that aim at the preservation of the environment.